Overexpression of Adenosine A2A Receptors in Rats: Effects on Depression, Locomotion, and Anxiety - Coelho, Joana E.; Alves, Pedro; Canas, Paula M.; Valadas, Jorge S.; Shmidt, Tatiana; Batalha, Vânia L.; Ferreira, Diana G.; Ribeiro, Joaquim A.; Bader, Michael; Cunha, Rodrigo A.; do Couto, Frederico Simões; Lopes, Luísa V. (Frontiers in Psychiatry, 2014)
Adenosine A2A receptors (A2AR) are a sub-type of receptors enriched in basal ganglia, activated by the neuromodulator adenosine, which interact with dopamine D2 receptors. Although this reciprocal antagonistic interaction is well established in motor function, the outcome in dopamine-related behaviors remains uncertain, in particular in depression and anxiety. We have demonstrated an upsurge of A2AR associated to aging and chronic stress. Furthermore, Alzheimer’s disease patients present A2AR accumulation in cortical areas together with depressive signs. We now tested the impact of overexpressing A2AR in forebrain neurons on dopamine related behavior, namely depression. Adult male rats overexpressing human A2AR under the control of CaMKII promoter [Tg(CaMKII-hA2AR)] and aged-matched wild-types (WT) of the same strain (Sprague-Dawley) were studied. The forced swimming test (FST), sucrose preference test (SPT) and the open-field test (OFT) were performed to evaluate behavioral despair, anhedonia, locomotion and anxiety. Tg(CaMKII-hA2AR) animals spent more time floating and less time swimming in the FST and presented a decreased sucrose preference at 48h in the SPT. They also covered higher distances in the OFT and spent more time in the central zone than the WT. The results indicate that Tg(CaMKII-hA2AR) rats exhibit depressive-like behavior, hyperlocomotion and altered exploratory behavior. This A2AR overexpression may explain the depressive signs found in aging, chronic stress and Alzheimer’s disease.